Biomechanics and finite element analysis comparing posterior T-plates with LCP for fixation of posterolateral tibial plate fractures - Hu, Zhenghui; Ren, Weizhi; Peng, Jian; Gu, Zenghui; Wu, Chenying; Wu, Weicheng; Zhang, Wen; Xu, Wei; Li, Liubing (Frontiers in Bioengineering and Biotechnology, 2023)
The treatment for posterolateral tibial plateau fractures (PTPF) have been subjects of controversy. We conducted a study to improve the fixation of PTPF through a lateral approach. We utilized 40 synthetic tibias and categorized the fracture models into five groups based on the locking compression plate (LCP) and Tdistal radius plate (TPP) via various forms of fixation with screws through the posterolateral (PL) fracture fragments. I: Two-screw fixation using two locking screws (LPTL). Ⅱ: Two-screw fixation with both variable angle locking screws (LPTV). Ⅲ: One-screw fixation with one locking screw (LPOL). Ⅳ: One-screw fixation with one locking screw and two anteroposterior lag screws (LPOLTL). Ⅴ: a distal radius plate with three locking screws (TPP). Biomechanical tests were conducted to observe the axial compression displacement of the PL fracture fragments at force levels of 250N, 500N, and 750N, as well as to determine the failure load and the axial stiffness for each respective group. Under a 750N load condition, the displacements within the five experimental groups exhibited the following trend: Ⅴ < Ⅱ < Ⅰ< Ⅳ < Ⅲ. However, there were no significant differences between Group V and Group II, Group I and Group IV (P > 0.05), and only Group Ⅲ demonstrated a displacement exceeding 3 mm. The failure load and the axial stiffness exhibited the same trend. Conversely, statistical significance was identified among the remaining group compared with Group Ⅲ (P < 0.05). Regarding the finite element analysis, the maximum displacements for the five models exhibited the following trend: Ⅴ < Ⅱ < Ⅰ< Ⅳ < Ⅲ. The following trends were observed in maximum von Mises stresses for these models: Ⅴ < Ⅱ < Ⅳ< Ⅰ < Ⅲ. It is crucial to address the inadequate mechanical strength associated with single screw fixation of LCP for fixing PL fractures in a clinical setting. The biomechanical strength of two-screw fixation surpasses that of single-screw fixation. Introducing variable-angle screws can further enhance the fixation range. Furthermore, the addition of two lag screws threaded from anterior to posterior can compensate the mechanical stability, when PL fracture is fixed with single screw in clinic.